A tale of the digital future: analyzing the digitalization of the norwegian education system. Issue 4 (1st November 2022) - Høydal, Øyunn Syrstad; Haldar, Marit
ABSTRACT: Schools are central in sustaining and extending values in society and therefore in shaping future society. While the global trend of education digitalization, commonly is presented as a depoliticized project of improvement, this paper seeks to uncover the values of the digital school as expressed in the strategy for the digitalization of the Norwegian education system. Inspired by Bacchi's ' WPR approach, the findings reveal that digitalization involves establishing a problem and a solution through discourses or narratives of education, working life, and the future.Given this problem representation and sociotechnical imaginary of the future, the school's main goal becomes to provide digitally competent future citizen-workers . The educational ideal of The Nordic model, and ideas of humanism and solidarity are not emphasized. Hence, the digital school reflects a neoliberal economy rather than values traditionally associated with the welfare state.